Sistema web para el manejo y control de información del taller automotriz el patio “Auto Spa” - Moposita Cazar, Pablo Josué (2024)
The present degree project was carried out in an automotive workshop located in the city of Ibarra, Imbabura province, Ecuador. This research aimed to address one of the problems that has affected the automotive workshop, specifically the lack of a system that facilitates the control and management of information related to its operation. To achieve this, a process of research and data collection was carried out in order to identify the necessary requirements for the implementation of an appropriate system. This process of obtaining information was crucial to understand the specific problems that the workshop was facing and find optimal solutions for each of them. Once the requirements were collected, the design and implementation of the information management system will be undertaken. This system will include different components, such as a database to store customer records, supplier information, inventory, and vehicle maintenance, as well as modules for report generation and activity tracking. The implementation of the system involves configuring hardware and software, as well as training the workshop staff for its proper use. Once implemented, the new information management system will enable the automotive workshop to optimize its processes, improve efficiency in customer service, have better control over inventory and suppliers, and generate accurate and up-to-date reports. Additionally, it will provide a centralized platform that facilitates access to and retrieval of information, contributing to informed decision-making and continuous improvement of workshop operations. In summary, this degree project was developed with the purpose of solving the problem of the lack of an information management system in an automotive workshop in Ibarra, Ecuador. Through an appropriate process of research and requirement analysis, a system will be implemented that optimizes workshop processes and improves overall efficiency.